Public-Private Partnership: High-Impact Alliance for Sustainability Targets - Y. I. Vaslavskiy (Vestnik MGIMO-Universiteta)
Efficient organization of public-private partnership (PPP) has become especially urgent amid the economic crisis caused by the COVID-19 pandemic and numerous sanctions imposed on the Russian Federation. The importance of this issue stems from the fact that the Russian economy has found itself at a crossing of at least two fundamental systemic transformations.On the one hand, all economic systems of the world, to a greater or lesser degree, have experienced limits to the development of a static economy. On the other hand, companies that have suffered the most from sanctions against Russia have leading-edge practices in organizing and participating in technological platforms and corporate ecosystems using B2C and B2B strategies. Therefore, a qualitative change in the economy to resolve the societal crisis is a universal challenge, and Russia is not the only country facing it.In this light, the transformation of the static economic system into a dynamic one moves up the agenda. Such change usually starts with building new structural ties by sustainable big companies that must conform to the dynamic reality. Dynamics for an economy mean new development perspectives and enormous expansion potential. This new status bases on the principles of human-centrism and an important new role for talented, intellectually autonomous individuals in corporate and other structures. This article outlines the author's interdisciplinary perspective on innovative and emerging evaluation knowledge and practice related to the environment, natural resources management, climate change, and development. In recent years, evaluation has emerged as an increasingly important function in determining the worth and value of development interventions in terms of their relevance, impact, performance, effectiveness, efficiency, and sustainability.We aspire to prove that PPP for Russia, following the pandemic-caused economic crisis and under Western sanctions, may perform a fundamental mission far more important than participation in producing public goods for budget funds. It could help the country to ensure a leap in its economy from statics to dynamics.This leap and respective transformations in corporate and social structures based on the human-centric principles could bring a multiplicative effect to the economy, quality of life, public policy, governance, and other spheres.